Kajian Keberkesanan Penggunaan Sistem Rumah Pintar IoT di Bandar Rimbayu, Kota Kemuning - Khairodin, Nurul Areeza Anastasia; Rosli, Mohd Arif; Mustafa, Mohd Syafiq Syazwan (Progress in Engineering Application and Technology, 2023)
IoT Smart Home System Technology is a new technology that able to connect with smart devices to interact with each other through the home network and contains several technological communications that can help from various aspects such as comfort, safety, security and convenience that allow an improvement in lifestyle of people. The objective of this study is to identify the differences in exposure to the use of IoT Smart Home Systems on the knowledge of residents in Rimbayu Town and to measure the level of effectiveness of IoT Smart Home System Technology in terms of privacy and security in Rimbayu Town, Kemuning City using a quantitative research method through a questionnaire which carried out in the area of ​​Bandar Rimbayu, Kota Kemuning which is a new sustainable community. This IoT Smart Home System technology proves to provide more benefits to the community to improve the quality of life from various aspects, especially aspects of privacy and security. This knowledge of IoT Smart Home System Technology can also foster community interest and therefore can increase the technology industry market in the future to continue to be trusted by users with control methods, advantages and purposes that can facilitate the public, especially the Malaysian community, so that they can be competitive with foreign countries.